WORK LIFE BALANCE IMPACT ON JOB BURNOUT (In case of concrete industry) - Gantsetseg, Zolzaya; Ganbaatar, Uyanga (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
This study explores the influence of work-life balance on job burnout. The research was conducted among 100 employees working at a concrete batching plant in Mongolia. The primary aim of the study is to emphasize the role of worklife balance as a significant underlying factor contributing to employee burnout. The findings reveal that when work interferes with personal life, and personal life interferes with work, burnout factors tend to increase. Conversely, when work and personal life positively reinforce each other, burnout levels decrease. Data were collected using a structured questionnaire distributed via an online tool (Google Forms), and statistical analysis was performed using the Stata software package.